Corundum mullite ceramic filter plate and preparation method thereof
By adopting the formulation and high-temperature sintering process of corundum mullite ceramic filter plates, the problem of ceramic filter plates being easily eroded in high-temperature aluminum liquid is solved, and high-efficiency filtration and low-cost ceramic filter plates are achieved.
Patent Information
- Application Number
- CN202411533691.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
AI Technical Summary
The existing ceramic filter plates are easily chemically eroded by magnesium during the high-temperature liquid aluminum filtration process, resulting in structural damage, reduced strength and reduced filtration accuracy, and there are problems of environmental pollution and high costs during production and use.
Corundum mullite ceramic filter plate, its formula includes corundum, microsilicon powder, cyanite, activated alumina powder, borax, silicon sol, citric acid and sintering aids, and mullite and aluminum borate are formed by high temperature sintering as Combining agent improves the mechanical strength and thermal shock performance of ceramic filter plates.
The ceramic filter plate does not erode with the alloy elements in the aluminum liquid at high temperatures, has high filtration accuracy and low residual aluminum content, which reduces the cost of use and solves the problem of environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of special ceramics and aluminum industry melt filtering and purification, in particular to a corundum-mullite ceramic filter plate and a preparation method thereof. Background Art
[0002] The filter medium of high-temperature aluminum liquid plate filtration is a ceramic filter plate of phosphate combined with alumina. The ceramic filter plate is produced by the impregnation method, with phosphate as a binder, which corrodes the production equipment of the filter plate. After use, the filter plate contains magnesium phosphide and aluminum phosphide, which produce phosphine toxic gas in contact with water, pollute the air, and the wastewater produced causes phosphorus pollution. In addition, the filter equipment will be preheated before filtration. During the preheating process, due to the large expansion coefficient of the material, large strength attenuation, and low residual strength, it is easy to be damaged during use.
[0003] When the high-temperature aluminum liquid to be filtered is a high-temperature molten aluminum-magnesium alloy, when the aluminum-magnesium alloy comes into contact with it, the magnesium element in the alloy and the phosphate undergo chemical corrosion, which destroys the structure of the ceramic filter plate and reduces its strength. It may even cause problems such as filter plate particle shedding, slag inclusion in the aluminum liquid, and casting failure. Moreover, after this type of filter plate has filtered the high-temperature aluminum liquid, a large amount of aluminum liquid remains in the internal pores, resulting in a high cost of use.
[0004] The Chinese invention patent with publication number CN115417681A, "A phosphorus-free, corrosion-resistant foam ceramic, its preparation method and application", uses high softening point glass as a binder and borides as raw materials. Borides and other raw materials form high softening point borosilicate glass at high temperatures, which solves the corrosion problem, but has poor thermal shock resistance and mechanical strength.
[0005] The Chinese invention patent with publication number CN116986919A, "A foam ceramic filter plate for high-cleanliness aluminum liquid purification and its preparation method", uses aluminum borate whiskers as a binder, which solves the corrosion problem of high-magnesium aluminum alloy and the thermal shock problem. However, due to its high aluminum borate content and the fact that aluminum borate produces a large liquid phase during the synthesis process and is accompanied by a large volume shrinkage, the product is easily deformed during the production process, the size is difficult to control, the cost is high, the yield is low, and the overall cost is 30-40% higher than the current alumina ceramic filter plate, making it difficult to promote and use.
[0006] Therefore, there is an urgent need for a corundum-mullite ceramic filter plate and a preparation method thereof to solve the above-mentioned technical problems. Summary of the invention
[0007] The purpose of the present invention is to improve the application scope and filtration accuracy of ceramic filter plates, solve the problem of chemical corrosion of magnesium in aluminum alloys, and meet the needs of high-magnesium aluminum alloy plate filtration; solve environmental problems during production and use, and erosion and breakage problems during use; improve filtration accuracy, reduce the amount of residual aluminum inside the filter plate, and reduce the cost of use.
[0008] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0009] A corundum-mullite ceramic filter plate comprises the following components in parts by weight:
[0010] 30-50 parts of corundum, 3-7 parts of microsilica powder, 10-15 parts of kyanite, 10-15 parts of activated alumina powder, 3-5 parts of borax, 8-16 parts of silica sol, 0.5-1.5 parts of citric acid, and 0.1-0.3 parts of sintering aid.
[0011] Preferably, the particle size of the corundum is 1000-2000 mesh.
[0012] The corundum in the components of the present invention is an ultrafine powder, which is used as an inert filler in the ceramic filter plate, has high stability at high temperatures, and does not react with metal elements in the high-temperature aluminum liquid.
[0013] Preferably, the microsilica powder is nano-microsilica powder.
[0014] Preferably, the average particle size of the activated alumina powder is 1 to 3 μm, wherein particles below 1 μm account for 60 to 70 wt%.
[0015] Nano-silica powder and activated alumina powder are mullitized at high temperature to form a mullite binder with high strength and good corrosion resistance.
[0016] Preferably, the particle size of the kyanite is 1000 mesh.
[0017] Preferably, the particle size of the borax is 5000 mesh.
[0018] Kyanite has good non-wetting properties with molten aluminum. Adding kyanite is beneficial to the separation of high-temperature molten aluminum and the ceramic filter plate, reducing the residual aluminum inside the ceramic filter plate after use; and reducing the cost of use.
[0019] Borax reacts with activated alumina powder at high temperature to produce needle-shaped aluminum borate whiskers, which are beneficial to improving the thermal shock resistance of the ceramic filter plate, reducing the high-temperature strength attenuation of the ceramic filter plate, and improving the preheating speed and use safety of the ceramic filter plate.
[0020] Preferably, the content of silicon dioxide in the silica sol is 20-40 wt%.
[0021] Silica sol provides low-temperature strength and medium-temperature strength in the entire formula system, maintains the shape and strength of the green body after drying, resists the shrinkage of the green body when the liquid phase is generated in the medium-temperature stage during the sintering process, and maintains the shape stability and dimensional accuracy of the green body.
[0022] Citric acid is used as a dispersant to improve the dispersion effect of the slurry during the pulping process, increase the solid content and stability of the slurry, and facilitate the uniform coating of the slurry on the sponge.
[0023] Preferably, the sintering aid is at least one of titanium oxide, aluminum fluoride and magnesium oxide.
[0024] In the formula system of the present invention, mullite and aluminum borate synthesized under high-temperature sintering are used as binders of inert materials. The binder does not corrode the alloy elements in the high-temperature aluminum liquid and has good mechanical strength and thermal shock resistance. After the kyanite is partially mullitized, it produces a slight volume expansion and forms a special structure in the internal pore structure of the ceramic filter plate, which is beneficial to the adsorption of impurity components in the high-temperature aluminum liquid and improves the filtration accuracy of the ceramic filter plate.
[0025] A method for preparing a corundum-mullite ceramic filter plate comprises the following steps:
[0026] The raw materials of various components of the corundum-mullite ceramic filter plate are uniformly mixed to obtain ceramic slurry, and the ceramic slurry is uniformly coated on a porous sponge by means of slurry dipping and extrusion, and then sintered after drying to obtain a ceramic filter plate.
[0027] Preferably, the components of the corundum-mullite ceramic filter plate are mixed and dispersed by high-speed dispersing equipment; the stirring speed during the dispersing process is 800-2000 r / min.
[0028] Preferably, the viscosity of the ceramic slurry is 5000-7000 cP.
[0029] Preferably, the drying temperature is 70-90°C, and the sintering temperature is 1000-1300°C. Further, the sintering temperature is 1200-1300°C.
[0030] Preferably, the sintering time is 60 to 400 minutes.
[0031] Preferably, the pore density of the porous sponge is 10 to 80 PPI.
[0032] Specifically, the method comprises the following steps: preparing the components of the corundum-mullite ceramic filter plate into a ceramic slurry by a high-speed dispersing device, with a dispersing speed of 800 to 2000 r / min, so that the ceramic slurry has good dispersibility and thixotropy, and the viscosity of the ceramic slurry is preferably 5000 to 7000 cP; uniformly coating the ceramic slurry on a porous sponge by slurry dipping (slurry dipping is a specific process operation in the impregnation process, which is a prior art and is well known to those skilled in the art, and will not be described in further detail here) and extruding, and then drying at 70 to 90° C.; and sintering at 1000 to 1300° C. after drying, wherein the sintering effect at 1200 to 1300° C. is better.
[0033] In the present invention, the methods of slurry impregnation and extrusion of the porous sponge can be adopted by the methods commonly used in the prior art, and no further limitation is imposed herein. The porous sponge can be selected from the methods commonly used in the art.
[0034] When traditional filter plates are applied to high-magnesium aluminum alloys such as 5 series and 7 series, they will be corroded, causing some particles to fall into the aluminum liquid, reducing the filtering accuracy; the filter plate obtained by the present invention has a wide range of applications, and can be used not only for filtering ordinary magnesium aluminum alloys, but also for filtering high-magnesium aluminum alloys.
[0035] Beneficial effects:
[0036] In the formula system of the present invention, mullite and aluminum borate synthesized under high-temperature sintering are used as binders of inert materials. The binder does not corrode the alloy elements in the high-temperature aluminum liquid and has good mechanical strength and thermal shock resistance. After the kyanite is partially mullitized, it produces a slight volume expansion and forms a special structure in the internal pore structure of the ceramic filter plate, which is beneficial to the adsorption of impurity components in the high-temperature aluminum liquid and improves the filtration accuracy of the ceramic filter plate. DETAILED DESCRIPTION
[0037] The present invention is further described below with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0038] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0039] There is no particular limitation on the purity of all raw materials in the present invention, and the present invention preferably adopts the conventional purity used in the art.
[0040] The devices used in the present invention are not particularly limited and can be any of the commonly used devices in the art.
[0041] In the following examples, the specific specifications of the components used are as follows:
[0042] The particle size of corundum is 1000-2000 mesh; the microsilica powder is nano-microsilica powder; the average particle size of activated alumina powder is 1-3 μm, of which particles below 1 μm account for 60-70wt%; the particle size of kyanite is 1000 mesh; the particle size of borax is 5000 mesh; the content of silicon dioxide in silica sol is 20-40wt%.
[0043] Example 1
[0044] A method for preparing a corundum-mullite ceramic filter plate comprises the following steps:
[0045] Weigh 30 parts of corundum powder, 3 parts of microsilica powder, 10 parts of kyanite, 10 parts of activated alumina powder, 3 parts of borax, 8 parts of silica sol, 0.5 parts of citric acid and 0.1 parts of titanium oxide in turn, disperse the above mixture at a speed of 1000r / min to make a pulp, use a 300mm×300mm×50mm porous sponge with a pore density of 30PPI to impregnate the pulp and extrude it, dry it at 90℃ and then sinter it at 1250℃ for 2h. The product has a ceramic filter plate with a size of 300mm×300mm×50mm. The compressive strength of the product is 3.4Mpa, the number of wind-cooled thermal shocks at 750℃ is 26 times, and the filtration effect of 5083 alloy with a magnesium content of 4% is 85%.
[0046] Example 2
[0047] A method for preparing a corundum-mullite ceramic filter plate comprises the following steps:
[0048] Weigh 50 parts of corundum powder, 5 parts of microsilica powder, 15 parts of kyanite, 15 parts of activated alumina powder, 5 parts of borax, 8 parts of silica sol, 1 part of citric acid and 0.2 part of titanium oxide in turn, disperse the above mixture at a speed of 1500r / min to make a pulp, use a 300mm×300mm×50mm porous sponge with a pore density of 60PPI to impregnate the pulp and extrude it, dry it at 85℃ and then sinter it at 1200℃ for 1h. The product has a ceramic filter plate with a size of 300mm×300mm×50mm. The compressive strength of the product is 4.2Mpa, the number of wind-cooled thermal shocks at 750℃ is 28 times, and the filtration effect of 5083 alloy with a magnesium content of 4% is 79%.
[0049] Example 3
[0050] A method for preparing a corundum-mullite ceramic filter plate comprises the following steps:
[0051] Weigh 37 parts of corundum powder, 4 parts of microsilica powder, 12 parts of kyanite, 12 parts of activated alumina powder, 4 parts of borax, 13 parts of silica sol, 1 part of citric acid and 0.3 part of magnesium oxide in turn, disperse the above mixture at a speed of 2000r / min to make a pulp, use a 300mm×300mm×50mm porous sponge with a pore density of 80PPI to impregnate and extrude it, dry it at 70℃ and then sinter it at 1200℃ for 1h. The product has a ceramic filter plate with a size of 300mm×300mm×50mm. The compressive strength of the product is 4.2Mpa, the number of wind-cooled thermal shocks at 750℃ is 28 times, and the filtration effect of 5083 alloy with a magnesium content of 4% is 85%.
[0052] Example 4
[0053] A method for preparing a corundum-mullite ceramic filter plate comprises the following steps:
[0054] Weigh 38 parts of corundum powder, 5 parts of microsilica powder, 12 parts of kyanite, 12 parts of activated alumina powder, 4 parts of borax, 13 parts of silica sol, 1 part of citric acid and 0.3 part of magnesium oxide in turn, disperse the above mixture at a speed of 1800r / min to make a pulp, use a 300mm×300mm×50mm porous sponge with a pore density of 80PPI to impregnate and extrude it, dry it at 80℃ and then sinter it at 1300℃ for 1h. The product has a ceramic filter plate size of 300mm×300mm×50mm. The compressive strength of the product is 5.3Mpa, the number of wind-cooled thermal shocks at 750℃ is 25 times, and the filtration effect of 5083 alloy with a magnesium content of 4% is 85%.
[0055] Comparative Example 1:
[0056] According to Example 2 of the Chinese invention patent "A Phosphorus-free Corrosion-resistant Foam Ceramic and Its Preparation Method and Application" with publication number CN115417681A: 2.5 parts of aluminum oxide, 4 parts of boric acid, and 0.25 parts of titanium oxide are taken, melted at 1450°C for 1.5 hours, quenched with water and ground to 2500 mesh to obtain component A; 6 parts of component A, 5 parts of mullite powder and kyanite powder with a particle size of 4000 mesh, 5 parts of ρ alumina and carboxymethyl cellulose with a particle size of 3000 mesh are taken; 1 part of cellulose and 9 parts of water are mixed evenly to obtain component B; a porous sponge of 300mm×300mm×50mm with a pore density of 80PPI is used for slurry impregnation and extrusion molding, and sintered at 1280℃ for 23h; the product has a ceramic filter plate of 300mm×300mm×50mm in size, and its compressive strength is 0.8Mpa, the number of wind-cooled thermal shocks at 750℃ is 3 times, and the filtration effect of 5083 alloy with a magnesium content of 4% is 73%.
[0057] Comparative Example 2:
[0058] The preparation was carried out according to the components and sintering temperature of Example 4 of the Chinese invention patent "A foam ceramic filter plate for purification of high-clean aluminum liquid and its preparation method" with publication number CN116986919A.
[0059] Take 5 parts by weight of mullite, 2 parts by weight of kyanite, 1 part by weight of quartz, 8 parts by weight of boric acid, 6 parts by weight of alumina, and 1 part by weight of dextrin, mix them in proportion, add 4 parts by weight of water to prepare a thixotropic ceramic slurry, use a 300mm×300mm×50mm porous sponge with a pore density of 80PPI for slurry impregnation and extrusion molding, and sinter at 1185°C for 60min; the product has a ceramic filter plate with a size of 295mm×298mm×49mm. After testing, its compressive strength is 1.5Mpa, the number of wind-cooled thermal shocks at 750°C is 8 times, and the filtration effect of 5083 alloy with a magnesium content of 4% is 75%.
[0060] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A corundum mullite ceramic filter plate, characterized in that: The composition comprises the following components in parts by weight: 30-50 parts of corundum, 3-7 parts of microsilica powder, 10-15 parts of kyanite, 10-15 parts of activated alumina powder, 3-5 parts of borax, 8-16 parts of silica sol, 0.5-1.5 parts of citric acid, and 0.1-0.3 parts of sintering aid.
2. The corundum-mullite ceramic filter plate according to claim 1, characterized in that: The particle size of the corundum is 1000-2000 meshes.
3. The corundum-mullite ceramic filter plate according to claim 1, characterized in that: The microsilica powder is nano-microsilica powder.
4. The corundum-mullite ceramic filter plate according to claim 1, characterized in that: The average particle size of the activated alumina powder is 1-3 μm, wherein particles below 1 μm account for 60-70 wt %.
5. The corundum-mullite ceramic filter plate according to claim 1, characterized in that: The particle size of the kyanite is 1000 mesh.
6. The corundum-mullite ceramic filter plate according to claim 1, characterized in that: The particle size of the borax is 5000 meshes.
7. The corundum-mullite ceramic filter plate according to claim 1, characterized in that: The content of silicon dioxide in the silica sol is 20-40 wt %.
8. The corundum-mullite ceramic filter plate according to claim 1, characterized in that: The sintering aid is at least one of titanium oxide, aluminum fluoride and magnesium oxide.
9. The method for preparing a corundum-mullite ceramic filter plate according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials of various components of the corundum-mullite ceramic filter plate are uniformly mixed to obtain ceramic slurry, and the ceramic slurry is uniformly coated on a porous sponge by means of slurry dipping and extrusion, and then sintered after drying to obtain a ceramic filter plate.
10. The method for preparing a corundum-mullite ceramic filter plate according to claim 9, characterized in that: The viscosity of the ceramic slurry is 5000-7000 cP; the drying temperature is 70-90° C.; and the sintering temperature is 1000-1300° C.
Citation Information
Patent Citations
Degassing filter box body and manufacturing method thereof
CN109516785A
Phosphorus-free corrosion-resistant foamed ceramic as well as preparation method and application thereof
CN115417681A
Foamed ceramic filter plate for purifying high-cleanliness molten aluminum and preparation method of foamed ceramic filter plate
CN116986919A
Ceramic powder composition, straight hole ceramic filter and preparation method therefor
WO2018006885A1
Cited By
Thermal shock resistant corundum-mullite multiphase heat storage ceramic material and preparation method thereof
CN120794585A